Effect of brief-intermittent hypoxic exposure on high-intensity kayaking and cycling performance - Bonetti, D. (2008)
Adaptation to the shortage of oxygen at altitude (hypoxia) promotes physiological changes which could enhance endurance performance. Consequently, altitude training has become a popular practice among competitive endurance athletes. Since its inception, the live-high train-low paradigm (LHTL) has been widely regarded as the most effective approach to altitude training. Over the past decade, brief intermittent simulation of LHTL via the use of hypoxic inhalers and re-breathing devices has gained increased popularity, but the evidence supporting their use is limited and conflicting. The experimental studies in this thesis investigated the response of sea level exercise performance and related physiological measures following adaptation to the usual and a novel protocol of brief intermittent hypoxia. I intended to perform all experimental studies on flat-water kayakers. Therefore, an initial requirement of this thesis was to establish the smallest worthwhile effect in performance for this sport. The final study utilising a meta-analytic approach was conducted to compare the effectiveness of brief intermittent hypoxia to other natural and simulated protocols, and to investigate the topical issue of what physiological responses mediate performance changes following hypoxic exposure. In Study 1, the typical variation in competitive performance of elite flat-water canoeists was investigated using a repeated-measures analysis of race times. For individual flat-water canoeing events, the smallest worthwhile change in performance time was ~0.5%. In two separate experimental studies, adaptation to 60 min per day of brief intermittent hypoxia consisting of alternating 5 min intervals of hypoxia and normoxia for 3 weeks (5 days per week) using a nitrogen filtration device resulted in clear enhancement of endurance performance (~5%) for kayakers (Study 2) and cyclists (Study 3). Clear enhancements in repeat sprint performance were observed for kayaking only. The physiological mechanisms underlying performance changes were unclear. Modification of the hypoxic and normoxic intervals (Study 3) did not result in any clear alterations in performance or physiological mechanisms. The meta-analysis (Study 4) revealed clear enhancements in endurance power output of 1-3% in sub-elites following adaptation to hypoxia with the natural altitude protocols, and with two of the artificial-altitude protocols (LHTL-long and LHTL-brief-intermittent). In elite athletes the enhancements tended to be smaller and were clear only for the natural protocols. These enhancements could be mediated by VO2max, although other mechanisms may be possible.